KARUNIA ROH DALAM JEMAAT KORINTUS - Tambunan, Debora Tiurlan (Shift Key : Jurnal Teologi dan Pelayanan, 2021)
AbstractThe gifts of the Spirit are understood as things given by the Holy Spirit to believers. However, they are often seen as something to be proud of. Also, there is a view that there are types of gifts of the Spirit which are more important and more spectacular than others. This study aims to find out what the real significance of the gifts of the Spirit in the ministry in the Corinthian church are through biblical qualitative methodology. It concludes that the gifts of the Spirit should bring Christocentric unity, motivate love, and build up the body of Christ.Â Keyword: Gifts of the Spirit, Corinthian, church, significanceÂ